The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5007/1980-0037.2017v19n6p676
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effectiveness of long distance passes in 2014 Brazil FIFA World Cup

Abstract: The aim of this study was to analyze the effectiveness of long distance passes performed during the 2014 Brazil FIFA World Cup. All 64 matches were analyzed, however, actions performed during overtime were not included in the sample. The study defined long pass as an action made by a player from the defensive midfield aiming at passing the ball to another teammate located on the offensive field. The action result assessment followed these criteria: shots on goal, ball possession maintenance, loss of ball posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…The reason might be that only quantity and not quality of crosses was considered. This assumption is supported by a study that found that long passes are linked to losing ball possession (Reis et al, 2017 ). Unsuccessful crosses are likely to initiate a counterattack.…”
Section: Discussionmentioning
confidence: 75%
“…The reason might be that only quantity and not quality of crosses was considered. This assumption is supported by a study that found that long passes are linked to losing ball possession (Reis et al, 2017 ). Unsuccessful crosses are likely to initiate a counterattack.…”
Section: Discussionmentioning
confidence: 75%
“…In the same way that authors claim that long passes are often ineffective and result in loss of ball possession (Reis et al, 2017), there are authors who consider ball possession a relevant performance indicator for success in soccer (Bate, 1988;Rocha-Lima, 2018;Stanhope, 2001). Complementarily, direct game approaches are also seen as beneficial for football teams at times when ball possession game models are not effective to win matches (Fernandez-Navarro et al, 2016;Tenga & Larsen, 2003), especially in the PL, league that the midfield consists of a fast passes area, not a control of the game one (Perarnau, 2017).…”
Section: Resultsmentioning
confidence: 95%
“…Além de ser uma das habilidades motoras que ocorre com maior frequência nos jogos, o passe permite o deslocamento da bola no campo, de jogador a jogador (CORRÊA et al, 2014;GOES et al, 2019;REIN;RAABE;MEMMERT, 2017). O passe pode ser caracterizado em função da localização, da direção, da velocidade e da distância da ação no campo de jogo (CORRÊA et al, 2014;GOES et al, 2019;VASCONCELLOS;ALMEIDA, 2017a).…”
Section: Introductionunclassified
“…No entanto, GOES et al(2019) não considerou as equipes de futebol como sistemas organizados hierarquicamente, além(GOES et al, 2019), no presente estudo esta habilidade motora foi investigada como variável informacional ou perturbação. Importa destacar que nenhum dos estudos supracitados(BULDÚ et al, 2019;CHMURA et al, 2021;IMMLER et al, 2021;LIU et al, 2015;LIU et al, 2016a;LIU et al, 2016b;MCLEAN et al, 2021;PRAÇA et al, 2019;VASCONCELLOS;ALMEIDA, 2017a;YI et al, 2022;YI et al, 2020a;YI et al, 2020b;YI et al, 2020c;YI et al, 2019a;YI et al, 2019b)investigaram o passe e suas características (localização, direção, distância e velocidade) como possíveis influências que poderiam causar mudanças na organização hierárquica das equipes de futebol.…”
unclassified